The Effectiveness of Using Viral Short Song from Tik Tok in Teaching Pronounciation: Efektivitas Penggunaan Lagu Pendek Viral dari Tik Tok dalam Pengajaran Pengucapan - Titik Nur Hidayanti Rahman; Iin Widya Lestari; Khoirul Wafa; Titik Nur Hidayanti Rahman; Iin Widya Lestari; Khoirul Wafa (INTENS (International Journal of English Education and Linguistics), 2024)
Pronunciation plays important part in oral communication. When learners start learning pronunciation they make new habits and overcome the difficulties performing from the first language. This study aimed to probe the impact of using the Viral Short Song as a training media on scholars' pronunciation chops. The disquisition was conducted among eight- grade scholars at SMP Plus Al hidayah Tuban. The disquisition was predicated on the premise that pronunciation is important aspect to communicate. Without accurate pronunciation, a word can be misread by the interlocutors. To address this issue, the disquisition explored the use of the viral short song, a training media designed to engage scholars in perfecting their recognition of delicate word and enhancing their interest in learning English. The disquisition employed anquasi-experimental design with a single subject group. Pre-tests andposttests were conducted to measure scholars' pronunciation chops ahead and after the performance of the viral short song. The results revealed a significant improvement in scholars' pronunciation chops following the treatment. Mean scores increased from a" truly Bad" type to a" truly Good" type, indicating the effectiveness of the viral short song in enhancing pronunciation. In conclusion, the study demonstrated that the viral short song is an effective fashion for perfecting scholars' pronunciation chops.